Addressable surface engineering for N-doped WS2 nanosheet arrays with abundant active sites and the optimal local electronic structure for enhanced hydrogen evolution reaction. Issue 44 (5th November 2020) - Wang, Haiqing; Xu, Zhongfei; Zhang, Zengfu; Hu, Shuxian; Ma, Mingjun; Zhang, Zhicheng; Zhou, Weijia; Liu, Hong
Abstract : Engineering an addressable surface endows N doped WS2 nanosheet arrays with abundant active sites and an optimal local electronic structure for enhanced hydrogen evolution reaction. Abstract : The precise control over the geometric and electronic structures of active materials on flexible substrates is of great importance to address the current challenges in optimizing and developing high-performance flexible devices for energy conversion and storage. In this work, an addressable surface was demonstrated to engineer structurally controllable active nanomaterials for electrocatalytic hydrogen evolution. The nanostructures of WS2 /MOF/metal hydroxide/oxide with different formation energy barriers electrodes could be tuned by modifying the ratio of O/C and the concentration of carbon defects at the surface of carbon cloth. The morphological structure of the vertical WS2 nanosheets that are favorable to electrocatalysis was found to be highly related to the addressable surface of carbon cloth though heterogeneous nucleation and the interactions between the monomers and surface functional groups. Moreover, the electronic structure of WS2 was further modified with N doping (N-WS2 ) to deliver an addressable surface for the reaction species involved in the electrocatalytic hydrogen evolution reaction (HER), and the resultant N-WS2 exhibited enhanced HER activity compared with the original WS2 . The systematic experimental research and electronic-structure density functional theory (DFT) calculations demonstrated the interesting features of the N dopant: (i) the strong hybridization of the p orbital of dopant N with d orbital of W and p orbital of S atoms (W d-S p-N p hybridization) close to the Fermi level can disperse the conducting charges, thus leading to an improved conductivity across the basal plane of WS2 nanosheets; (ii) the local electron transfer from W to N atoms provides the local charge, thus promoting the H adsorption process in the HER for N-WS2 . Our research can be expected to offer new perspectives in the precise construction of highly reactive nanostructures toward high-efficiency and highly stable flexible devices for energy conversion and storage.